Elevated Myl9 reflects the Myl9-containing microthrombi in SARS-CoV-2–induced lung exudative vasculitis and predicts COVID-19 severity - Iwamura, Chiaki; Hirahara, Kiyoshi; Kiuchi, Masahiro; Ikehara, Sanae; Azuma, Kazuhiko; Shimada, Tadanaga; Kuriyama, Sachiko; Ohki, Syota; Yamamoto, Emiri; Inaba, Yosuke; Shiko, Yuki; Aoki, Ami; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
The mortality of coronavirus disease 2019 (COVID-19) is strongly correlated with pulmonary vascular pathology accompanied by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection–triggered immune dysregulation and aberrant activation of platelets. We combined histological analyses using field emission scanning electron microscopy with energy-dispersive X-ray spectroscopy analyses of the lungs from autopsy samples and single-cell RNA sequencing of peripheral blood mononuclear cells to investigate the pathogenesis of vasculitis and immunothrombosis in COVID-19. We found that SARS-CoV-2 accumulated in the pulmonary vessels, causing exudative vasculitis accompanied by the emergence of thrombospondin-1–expressing noncanonical monocytes and the formation of myosin light chain 9 (Myl9)–containing microthrombi in the lung of COVID-19 patients with fatal disease. The amount of plasma Myl9 in COVID-19 was correlated with the clinical severity, and measuring plasma Myl9 together with other markers allowed us to predict the severity of the disease more accurately. This study provides detailed insight into the pathogenesis of vasculitis and immunothrombosis, which may lead to optimal medical treatment for COVID-19.